La estética del "plagio" en "El Quijote" - Cuesta Torre, María Luzdivina (Estudios Humanísticos. Filología, 1997)
There are some resemblances in themes, topics, humour and parodie attitude between the Tristán edition of 1534 and El Quijote. This is a study about these resemblances and their signification.